The Acceptability of the Proposed Design of Bungang-Api Park: Community Aquaculture Chinampas Utilizing Avicennia Officinalis as Crop Support - Ravis, Shane D. (International Journal of Environment, Engineering and Education, 2024)
Chinampas are an effective way to increase access to new crop resources that benefit ecosystems, sustainability, livelihood, and food security. Chinampas are rectangular mud-artificial islands built in bodies of water where crops are grown. They are typically constructed of willow trees, and only one native can be found in the Philippines. Using Avicennia officialnalis, also known as Api-API, which grows in firm mud as a substitute for willow trees, along with landscape architecture, the integration of green space, mangrove nurseries for reforestation, and the reduction of aquaculture—a significant cause of mangrove loss—is a potential building for chinampas in the Philippines setting. The study aims to determine whether a design is acceptable to the residents of the chosen setting and proposed design, Barangay Sto Rosario, Paombong, Bulacan, Philippines, in terms of (1) area usability, (2) design appreciation, and (3) environment, with 264 samples responding to a validated questionnaire consisting of 13 Likert scale questions for quantitative data and three open-ended questions, extracted with thematic analysis for qualitative data. In the research setting, 148 respondents were required to complete the survey. The results show that the design is acceptable. Some aspects were low, but due to the respondents' unawareness of the field and objective of design and landscape architecture, it appears to be welcoming to the respondents' acknowledgement. Respondents also input their perspectives and thoughts about its possibilities for economic values, the full potential of green spaces, and its feasibility and promotion of biodiversity.